In the Workshop of a Stationer in Florence, in the Year 1348 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
In this contribution, a document preserved in the Florence State Archives is presented, relating to a legal case recorded between July 1348 and January 1349, in which the stationer Orsello di Andrea Orselli filed a lawsuit against the heirs of Vieri di Giovanni for a debt of 13 gold florins. On September 17, 1348, the judge Vanni di Giovanni ordered the seizure of the goods in Vieri's shop to cover the claimed amount, following the judicial customs of the time. The goods were appraised by Filippino di Filippo Vannozzi, also a stationer, who listed and assigned a value to each item, including paper notebooks, parchment, and tools. A second creditor, the linen merchant Ristoro Niccoli, also obtained a seizure on the same goods for a debt of 9 florins. The total debt amounted to 22 florins and 50 soldi, while the value of the seized goods was 68 lire and 16 soldi, almost exactly matching the owed amount. At the end of the trial, the objects were awarded to Orsello as part of the debt settlement. This case provides valuable insights into the valuation of goods in a 14th-century stationer's shop in Florence and the high cost of paper compared to parchment.
Keywords: Judicial Seizure; Stationer's Shop; Goods Appraisal; Commercial Debt; State Archives